2023
DOI: 10.1088/1742-6596/2430/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Wet-Preparation Methods of Nickel Foam For Alkaline Water Electrolysis

Abstract: Water electrolysers are multi-component systems whose performance relies on each part performing its task. A great emphasis has been placed on the development of efficient catalyst-coated electrodes, however the efficacy of the underlying substrate itself has been overlooked. This paper investigates the resulting performance of nickel foam electrodes in 1.0 M KOH after being treated in various concentrations of hydrochloric acid and sulphuric acid. The greatest performance was achieved utilising 0.50 M H2SO4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…1 The key factors that control the electrocatalytic performance of an electrode are the electrical conductivity of the substrate itself and the extent of charge transport between the interface of the electrode surface and the deposited catalyst material (heterogeneous). 2 To make this charge/electron transport more facile, the choice of the electrode substrate plays a central role and is important in terms of its stability and activity in harsh conditions. Considering low-cost, better charge/electron mobility, high specific surface area, and superior aqueous stability, three-dimensional (3-D) nickel foam (NF) is widely used as an electrode substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 The key factors that control the electrocatalytic performance of an electrode are the electrical conductivity of the substrate itself and the extent of charge transport between the interface of the electrode surface and the deposited catalyst material (heterogeneous). 2 To make this charge/electron transport more facile, the choice of the electrode substrate plays a central role and is important in terms of its stability and activity in harsh conditions. Considering low-cost, better charge/electron mobility, high specific surface area, and superior aqueous stability, three-dimensional (3-D) nickel foam (NF) is widely used as an electrode substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The electrocatalytic HER study of such acid-pretreated NF exhibited better activity when a higher acid concentration was chosen for the pretreatment. 2 In the majority of published works, after the acid treatment, NF was not characterized and the effect of acid treatment was not carefully analyzed. However, Yeo et al reported that the OER process under alkaline conditions leads to the formation of the γ-NiO(OH) phase on bulk Ni, identified through in situ Raman spectra analysis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations